2017
DOI: 10.1002/pbc.26891
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hepatotoxicity and pancreatitis in children and adolescents with acute lymphoblastic leukemia treated according to contemporary regimens

Abstract: Obese and/or older children are particularly at risk for hepatotoxicity and pancreatitis, and may benefit from toxicity surveillance and chemoprotective strategies to prevent or mitigate associated morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 58 publications
7
68
2
Order By: Relevance
“…The cumulative risk of pancreatitis in our cohort was similar to that found in previously published results in asparaginase intensive protocols . Our failure to reproduce the association between BMI and risk of pancreatitis could be attributable to type 2 error due to a limited number of patients in the overweight and obese groups, though the total cohort was four times larger than the cohort used by Denton et al …”
Section: Baseline Characteristics and Cumulative Incidences Of Pancresupporting
confidence: 77%
See 2 more Smart Citations
“…The cumulative risk of pancreatitis in our cohort was similar to that found in previously published results in asparaginase intensive protocols . Our failure to reproduce the association between BMI and risk of pancreatitis could be attributable to type 2 error due to a limited number of patients in the overweight and obese groups, though the total cohort was four times larger than the cohort used by Denton et al …”
Section: Baseline Characteristics and Cumulative Incidences Of Pancresupporting
confidence: 77%
“…Using comprehensible inclusion criteria with prospective registration of pancreatitis in a large well‐described cohort, all following the same treatment protocol, we were unable to reproduce the association between obesity and risk of pancreatitis but were able to produce the well‐known, increased risk of pancreatitis for adolescents with ALL . The cumulative risk of pancreatitis in our cohort was similar to that found in previously published results in asparaginase intensive protocols .…”
Section: Baseline Characteristics and Cumulative Incidences Of Pancresupporting
confidence: 51%
See 1 more Smart Citation
“…Hepatotoxicity is a common treatment-related toxicity (TRT) during contemporary treatment regimens for ALL. Denton et al (10) identified 262 patients, of whom 71 (27%) developed hepatotoxicity. Approximately 25% of hepatotoxicities (18/71) occurred during induction alone.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and metabolic dysfunction play a major role in survivors of childhood ALL leading to increased risk of morbidity and mortality throughout their life [3][4][5][6]. Altered lipid metabolism caused by intensive therapy has been addressed [7][8][9][10][11] and contradictory associations to toxicities such as thromboembolism [12][13][14][15], osteonecrosis [16,17] and pancreatitis [18][19][20][21][22][23][24] have been reported. Furthermore, abnormal lipid levels prior to ALL therapy [25][26][27][28][29] and obesity at time of ALL-diagnosis have been associated with reduced efficacy of induction therapy, impaired event-free and overall survival [30][31][32] as well as suggested as a part of the leukomogenisis [33].…”
Section: Introductionmentioning
confidence: 99%